(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the importance of legal culture in developing entrepreneurs’ legal knowledge and skills in modern conditions, the development of legal culture in the professional culture of entrepreneurs within the context of the knowledge system, understanding and application of industry legislation, the functional objectives of entrepreneurial activity, as well as the actors of innovative and intellectual activity in the formation of a social, rule-of-law state, and their direct and indirect needs.